The work characteristics and social distancing at the manufacturing workplace - Keisuke Kokubun (Cogent Business & Management, 2022)
The spread of new coronavirus (COVID-19) infections shows no signs of stopping. Therefore, we must consider how to deal with this disaster well. The practice of social distance is one of the powerful tools for that purpose. Therefore, in this paper, we analyzed the factors that influence physical proximity in the manufacturing industry, which has a large impact on the economy given the scale of employment. As the method, first, exploratory factor analysis is performed using the US occupation information site O*NET information, and the extracted 7 variables, sitting work, work conditions, information processing, task significance, interdependence, response to aggression, and autonomy, are used in the regression analysis. As a result, it was shown that interdependence and response to aggression, which are categorized as "social characteristics", and work conditions and sitting work, which are categorized as "context characteristics", showed a positive correlation with physical proximity.
Keywords: 650; exploratory factor analysis; New Coronavirus (COVID-19); O*NET; physical proximity; social distancing; work characteristics